Gendered Risk Perceptions Associated with Human-Wildlife Conflict: Implications for Participatory Conservation - Gore, Meredith L.; Kahler, Jessica S. (PLOS ONE, 2012)
This research aims to foster discourse about the extent to which gender is important to consider within the context of participatory approaches for biological conservation. Our objectives are to: (1) gender-disaggregate data about stakeholders' risk perceptions associated with human-wildlife conflict (HWC) in a participatory conservation context, and (2) highlight insights from characterizing gendered similarities and differences in the way people think about HWC-related risks. Two communal conservancies in Caprivi, Namibia served as case study sites. We analyzed data from focus groups (n = 2) to create gendered concept maps about risks to wildlife and livelihoods and any associations of those risks with HWC, and semi-structured interviews (n = 76; men = 38, women = 38) to measure explicit risk attitudes associated with HWC. Concept maps indicated some divergent perceptions in how groups characterized risks to wildlife and livelihoods; however, not only were identified risks to wildlife (e.g., pollution, hunting) dissimilar in some instances, descriptions of risks varied as well. Study groups reported similar risk perceptions associated with HWC with the exception of worry associated with HWC effects on local livelihoods. Gendered differences in risk perceptions may signal different priorities or incentives to participate in efforts to resolve HWC-related risks. Thus, although shared goals and interests may seem to be an obvious reason for cooperative wildlife management, it is not always obvious that management goals are shared. Opportunity exists to move beyond thinking about gender as an explanatory variable for understanding how different groups think about participating in conservation activities.